"For better or for worse" – the role of family ownership in the resilience of rural hospitality firms. Issue 1 (1st January 2020) - Engeset, Agnes Brudvik
ABSTRACT: Family business research has identified contributing factors to the dominance of family firms in the tourism industry worldwide. The tourism literature, however, has focused more on start-ups than on long-term survival, especially in areas of rural tourism. Thus more knowledge is needed of how family ownership contributes to the resilience of hospitality firms. In rural Europe, many family-owned hotels that have existed for generations are now struggling to survive. However, some family-owned rural hotels are still performing well. This study uses interviews with ten former and present hotel owners to explore how family businesses respond to various challenges and how family ownership has influenced the survival of rural hotels. Drawing on research into tourism business resilience and family businesses, the study suggests that the resilience of rural hotels depends on family capital. This is in line with previous studies of family firm resilience outside of the tourism and hospitality context. The scientific contribution of this paper is the identification of components of human and social capital that build resilience in rural hospitality. The findings may advance hospitality management by recognising the family members' important contributions to long-term survival of family firms.